EDITORS’ NOTE (The Pretoria Student Law Review, 2021)
This year’s edition includes a diverse range of articles. Some are close to home while others grapple with issues abroad. From feminism & queer theory, to child rights, sports law, free higher education, and of course, the language debate, our authors have ensured that every reader will find something to both challenge and broaden their minds.